Effects of Betaine Supplementation on Live Performance, Selected Blood Parameters, and Expression of Water Channel and Stress-Related mRNA Transcripts of Delayed Placement Broiler Chicks - Al-Sagan, Ahmed Abdulaziz; Al-Abdullatif, Abdulaziz; Hussein, Elsayed O. S.; Saadeldin, Islam M.; Al-Mufarrej, Saud I.; Qaid, Mohammed; Albaadani, Hani H.; Swelum, Ayman Abdel-Aziz; Alhotan, Rashed (Frontiers in Veterinary Science, 2021)
This study examined the effect of supplemental betaine on live performance, selected blood parameters, and gene expression of water channel proteins (Aquaporins, AQP) of broiler chicks delayed in placement for 48 h post-hatch. In total, 540 newly-hatched male broiler chicks were obtained from a local hatchery and were randomly allotted to one of five treatments with nine replicates per treatment (12 chicks per replicate). Chicks were either placed immediately, control; held for 48 h post-hatch with no access to feed or water, Holdnull; held for 48 h with free access to drinking water only, HoldW; held for 48 h with free access to drinking water supplemented with 1 ml per L of betaine solution (40% betaine), HoldB1; or held for 48 h with free access to drinking water supplemented with 2 ml per L of betaine solution (40% betaine), HoldB2 group. The results showed that post-hatch holding for 48 h depressed feed intake and body weight gain during the entire 15 d study period with no beneficial effect of supplemental betaine. Chicks in the HoldB2 group had elevated serum glucose, triglycerides, and aspartate aminotransferase 48 h post-hatch. Early water deprivation directly affected the brain proopiomelanocortin (POMC) and hepatic glucocorticoid receptors (GR) expression and induced significant changes in various aquaporins (AQP1, AQP2, AQP4, and AQP9). In conclusion, betaine supplementation to chicks held for 48 h post-hatch resulted in some changes in blood biochemical indices with no effects on performance during the first 15 days of life. The results suggest that betaine supplementation could ameliorate the stressful effects of water deprivation on POMC and GR expression and maintain cellular osmosis through interactions with variable aquaporins expression, particularly the AQP1 and AQP2. Further investigations are required to investigate the molecular mechanisms underlying the selective regulatory expression of different aquaporins in relation to betaine supplementation.